Characterisation of flavour-texture interactions in sugar-free and sugar-containing pectin gels. - Tyapkova, Oxana; Bader-Mittermaier, Stephanie; Schweiggert-Weisz, Ute; Wurzinger, Sandrina; Beauchamp, Jonathan; Büttner, Andrea (Food Research International, 2014)
The influences of sugar replacement with erythritol or erythritol/sucralose on textural properties (hardness and visco-elastic behaviour) and flavour release of low ester pectin gels containing 0.04% or 0.12% (w/w) calcium citrate were analysed. Flavour release of (Z)-hex-3-en-1-ol (cis-3-hexenol), benzaldehyde, ethyl butanoate and 2-methylpropyl 3-methylbutanoate (isobutyl isovalerate) was determined using proton-transfer-reaction mass spectrometry (PTR-MS). In-vitro studies showed that the replacement of sucrose with erythritol did not influence flavour release, whereas the release tended to be higher and faster for erythritol- or erythritol/sucralose-containing gels during in-vivo measurements. Additionally, different flavour release patterns were obtained between harder and softer pectin gels during in-vivo measurements, while only release of isobutyl isovalerate was significantly different during in-vitro analysis. The sensory analysis exhibited significant differences between the flavoured pectin gels with similar textures, confirming the results of PTR-MS measurements. Generally, flavour perception was reduced with increased gel hardness independently of the nose-space concentrations, reflecting perceptual interactions between texture and flavou